2014
DOI: 10.1586/14789450.2014.901892
|View full text |Cite
|
Sign up to set email alerts
|

The role of apolipoprotein E in neurodegeneration and cardiovascular disease

Abstract: Apolipoprotein E (ApoE) is an abundant plasma protein that interacts with low density lipoprotein receptors and other proteins, participating in the transport of cholesterol and lipids. Research has revealed many other roles for this multifunctional protein. ApoE is polymorphic and exists in three major isoforms: ApoE2, ApoE3 (the most common isoform) and ApoE4, which differ by only one amino acid, at positions 112 and 158. The altered binding to lipids and receptors by ApoE isoforms E2 and E4 results in an el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 83 publications
0
22
0
3
Order By: Relevance
“…Alzheimer’s disease, cerebrovascular disease, and cardiovascular disease have shared genetic contributions [76,77], and approximately 50% of individuals diagnosed with Alzheimer’s disease display significant cerebrovascular pathology on autopsy [78,79]. Together, these findings suggest that cardiovascular disease, Alzheimer’s disease, and vascular dementia may have an overlapping pathophysiology [8082].…”
Section: Dementia Risk and Hypertensionmentioning
confidence: 99%
“…Alzheimer’s disease, cerebrovascular disease, and cardiovascular disease have shared genetic contributions [76,77], and approximately 50% of individuals diagnosed with Alzheimer’s disease display significant cerebrovascular pathology on autopsy [78,79]. Together, these findings suggest that cardiovascular disease, Alzheimer’s disease, and vascular dementia may have an overlapping pathophysiology [8082].…”
Section: Dementia Risk and Hypertensionmentioning
confidence: 99%
“…ApoE is a polymorphic protein with common variants known as E2, E3, and E4 that are encoded by the ε2, ε3, and ε4 alleles, respectively, with population frequencies of approximately 8, 77 and 15%, respectively [97][98][99]. ApoE4 has been confirmed as an important factor for dementia and progress of cognitive impairment in the elderly [100,101].…”
Section: Insulin Resistance and The Apoe ε4 Allelementioning
confidence: 99%
“…Evidence was provided by a previous study that elevated plasma lipid was the main risk for cardiovascular disease and ApoE polymorphisms influence the lipid composition in plasma and the progression of cardiovascular disease through other biochemical pathway [11]. Zhang et al [35] observed that ε4 allele exerted a high risk on Chinese coronary heart disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…And cardiovascular complications have been demonstrated as a main cause of morbidity and mortality in patients with kidney failure [10]. Interestingly, it has been reported that apolipoprotein E (ApoE) is a genetic risk factor for some cardiovascular diseases, such as myocardial infarction and coronary artery disease [11].…”
Section: Introductionmentioning
confidence: 99%